DILEMA PERLINDUNGAN HUKUM: KETERBATASAN EFEKTIVITAS PRODUK HUKUM DAERAH DALAM MENJAMIN HAK-HAK MASYARAKAT ADAT - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2025)
This study discusses the dilemma of legal protection for indigenous peoples in Indonesia that has arisen due to the limited effectiveness of regional legal products in guaranteeing their rights. Although a number of regional legal products have been issued as an effort to recognise and protect them, their implementation has often failed to provide substantial and sustainable protection. The main obstacles identified include overlapping authority between the central and regional governments, complex bureaucracy, political and economic pressures, and a lack of regulatory harmonisation. These conditions result in legal uncertainty that is detrimental to indigenous peoples, particularly in relation to the recognition of customary territories, land rights, and cultural preservation. Through a literature review, this study outlines the national legal framework and local legal products, and examines the limiting factors and real implications for the rights of indigenous peoples. The results of the study emphasise the importance of policy harmonisation, synergy between governments, and strengthening the national legal framework to improve the effectiveness of legal protection and ensure social justice for indigenous peoples.